Hepatobiliary disease in children and adolescents with cystic fibrosis - Fernanda de S. Nascimento; Nelson A. Sena; Tatiane da A. Ferreira; Cibele D.F. Marques; Luciana R. Silva; Edna Lúcia Souza (Elsevier, 2018)
Objectives: The aims of the study were to determine the frequency of hepatobiliary disease in patients with cystic fibrosis and to describe the sociodemographic, clinical, and laboratory profile of these patients. Methods: This was a retrospective, descriptive, and analytical study of 55 patients diagnosed with cystic fibrosis, aged between 3 months and 21 years, followed-up from January 2008 to June 2016 in a referral center. Medical records were consulted and sociodemographic, clinical and laboratory data, including hepatobiliary alterations, imaging studies, genetic studies, liver biopsies, and upper digestive endoscopies were registered. Results: Hepatobiliary disease was diagnosed in 16.4% of the patients and occurred as an initial manifestation of cystic fibrosis in 55.6% of these cases. The diagnosis of hepatopathy occurred before or concomitantly with the diagnosis of cystic fibrosis in 88.9% of the children. All patients with hepatobiliary disease were considered non-white, with a predominance of females (77.8%) and median (IQR) of 54 (27-91) months. Compared with the group without hepatobiliary disease, children with liver disease had a higher frequency of severe mutations identified in the CFTR gene (77.8% vs. 39.6%, p = 0.033) and severe pancreatic insufficiency (88.9% vs. 31.6%, p = 0.007). Conclusion: The frequency of hepatobiliary disease was high, with a very early diagnosis of the disease and its complications in the studied series. A statistical association was observed between the occurrence of hepatobiliary disease and the presence of pancreatic insufficiency and severe mutations in the CFTR gene. It is emphasized that cystic fibrosis is an important differential diagnosis of liver diseases in childhood. Resumo: Objetivos: Os objetivos do estudo foram determinar a frequência da doença hepatobiliar em pacientes com fibrose cística e descrever o perfil sociodemográfico, clínico e laboratorial destes. Métodos: Estudo retrospectivo, descritivo e analítico de 55 pacientes com diagnóstico de fibrose cística, entre três meses e 21 anos, acompanhados de janeiro de 2008 a junho de 2016 em um centro de referência. Foi realizada consulta aos prontuários médicos, registrando-se os dados sociodemográficos, clínicos e laboratoriais, incluindo-se alterações hepatobiliares, exames de imagem, estudos genéticos, biópsias hepáticas e endoscopias digestivas altas. Resultados: A doença hepatobiliar foi diagnosticada em 16,4% dos pacientes e ocorreu como manifestação inicial da fibrose cística em 55,6% destes casos. O diagnóstico da hepatopatia ocorreu antes ou concomitante ao diagnóstico da fibrose cística em 88,9% das crianças. Todos os pacientes com doença hepatobiliar foram considerados não brancos, havendo predominância do sexo feminino (77,8%) e mediana (I.I.Q) de idade de 54 (27-91) meses. Em comparação com o grupo sem doença hepatobiliar, as crianças com hepatopatia tiveram maior frequência de mutações graves no gene CFTR identificadas (77,8% vs 39,6%; p = 0,033) e de insuficiência pancreática grave (88,9% vs 31,6%; p = 0,007). Conclusão: A frequência de doença hepatobiliar foi elevada, observando-se um diagnóstico muito precoce da mesma e de suas complicações na casuística estudada. Houve associação estatística entre a ocorrência de doença hepatobiliar e a presença de insuficiência pancreática e de mutações graves do gene CFTR. Enfatiza-se que a fibrose cística represente um importante diagnóstico diferencial de hepatopatias na infância. Keywords: Mucoviscidosis, Hepatopathies, Liver, Palavras-chave: Mucoviscidose, Hepatopatias, Fígado